A second‐generation genetic linkage map for bighead carp (Aristichthys nobilis) based on microsatellite markers. (14th July 2014) - Zhu, C.; Tong, J.; Yu, X.; Guo, W.; Wang, X.; Liu, H.; Feng, X.; Sun, Y.; Liu, L.; Fu, B.
Summary Bighead carp (Aristichthys nobilis) is an important aquaculture fish worldwide. Genetic linkage maps for the species were previously reported, but map resolution remained to be improved. In this study, a second‐generation genetic linkage map was constructed for bighead carp through a pseudo‐testcross strategy using interspecific hybrids between bighead carp and silver carp. Of the 754 microsatellites genotyped in two interspecific mapping families (with 77 progenies for each family), 659 markers were assigned to 24 linkage groups, which were equal to the chromosome numbers of the haploid genome. The consensus map spanned 1917.3 cM covering 92.8% of the estimated bighead carp genome with an average marker interval of 2.9 cM. The length of linkage groups ranged from 52.2 to 133.5 cM with an average of 79.9 cM. The number of markers per linkage group varied from 11 to 55 with an average of 27.5 per linkage group. Normality tests on interval distances of the map showed a non‐normal marker distribution; however, significant correlation was found between the length of linkage group and the number of markers below the 0.01 significance level (two‐tailed). The length of the female map was 1.12 times that of the male map, and the average recombination ratio of female to male was 1.10:1. Visual inspection showed that distorted markers gathered in some linkage groups and in certain regions of the male and female maps. This well‐defined genetic linkage map will provide a basic framework for further genome mapping of quantitative traits, comparative mapping and marker‐assisted breeding in bighead carp.